Springs of the Flint Hills - Rex Buchanan; Bob Swain; Wayne Lebsack (Symphony in the Flint Hills, 2009)
Jack Spring is a prairie oasis. Tucked away in southwestern Chase County, it's only a few miles from the Kansas Turnpike, but a world away in terms of the setting. The spring spills out of dark openings in a limestone bluff, then drops down into a creek choked with bright green watercress. Minnows dart in the water. Leaves rustle in the cottonwoods.
Keywords: spring; water; native; animals; people; Flint Hills; river; creek; landscape; mineral water; Chingawassa Springs